2020
DOI: 10.1002/mrd.23408
|View full text |Cite
|
Sign up to set email alerts
|

Changes in porcine cauda epididymal fluid proteome by disrupting the HPT axis: Unveiling potential mechanisms of male infertility

Abstract: Male infertility or subfertility is frequently associated with disruption of the hypothalamic-pituitary-testis axis events, like secondary hypogonadism. However, little is known how this condition affects the proteomic composition of the epididymal fluid. In the present study, we evaluated the proteomic changes in the cauda epididymal fluid (CEF) in a swine model of secondary hypogonadism induced by anti-GnRH immunization using multidimensional protein identification technology. Seven hundred and eighteen prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
(87 reference statements)
2
1
0
Order By: Relevance
“…20 Evidence also supports the use of IC boars as a model for the study of secondary hypogonadism in humans. [21][22][23] Regression of the reproductive tract in immunocastrated male pubertal pigs is consistent with a loss of functional activity, as shown by the histological changes in testicular tissue. [24][25][26] Research findings suggest that the timing of vaccination (during either early or late sexual development stage) may play a crucial role in the extent of suppression of reproductive function 25 ; however, the underlying physiological mechanisms are unclear and merit further investigation.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…20 Evidence also supports the use of IC boars as a model for the study of secondary hypogonadism in humans. [21][22][23] Regression of the reproductive tract in immunocastrated male pubertal pigs is consistent with a loss of functional activity, as shown by the histological changes in testicular tissue. [24][25][26] Research findings suggest that the timing of vaccination (during either early or late sexual development stage) may play a crucial role in the extent of suppression of reproductive function 25 ; however, the underlying physiological mechanisms are unclear and merit further investigation.…”
Section: Introductionsupporting
confidence: 55%
“…This is equivalent to pigs been suggested as a suitable animal model for translational research because of the similarities in their reproductive processes with those of humans 20 . Evidence also supports the use of IC boars as a model for the study of secondary hypogonadism in humans 21–23 . Regression of the reproductive tract in immunocastrated male pubertal pigs is consistent with a loss of functional activity, as shown by the histological changes in testicular tissue 24–26 .…”
Section: Introductionsupporting
confidence: 53%
“…Currently, it had been demonstrated that sperm in the epididymal corpus area possess a similar ability to cauda sperm, including capacitation, oocyte fertilization, and survival during cryopreservation ( Kunkitti et al, 2015 ; Kunkitti et al, 2016a ; Kunkitti et al, 2016b ). The cauda of the epididymis served as the final storage site for matured sperm prior to ejaculation ( Souza et al, 2020 ). In many animal species, sperm could maintain fertility for several weeks within this environment ( Esponda and Bedford, 1986 ).…”
Section: Regional Segmentation and Functional Differentiation In Epid...mentioning
confidence: 99%